1999
DOI: 10.1002/(sici)1520-6327(199912)42:4<245::aid-arch3>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an insect neuropeptide,Schistocerca gregaria ion transport peptide (ITP), expressed in insect cell systems

Abstract: We have produced an active form of Schistocerca gregaria ion transport peptide (ITP) in an insect cell expression system. Transformed Drosophila Kc1 cells secreted a form of ITP into the cell culture medium that was proteolytically cleaved correctly at the amino (N)‐terminus. Concentrated culture supernatant from transformed Kc1 and Hi5 cells had high biological activity when tested on isolated locust ilea. Conversely, ITP expressed by baculovirus‐infected Sf9 cells was larger in size and had decreased specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
2
10
0
Order By: Relevance
“…1B,C,E,F) and may indicate a post-translational modification of one or more amino acids common to all these expressed peptides (Tables 1,2). The amino acid sequence of the first 22 residues of both bands was identical, as reported by Pfeifer et al (1999). Figure 1B and C compare Western blots of supernants from Kc1 cells transformed with preproITP cDNAs in which successive C-terminal amino acids were removed.…”
Section: Bioassayssupporting
confidence: 66%
See 2 more Smart Citations
“…1B,C,E,F) and may indicate a post-translational modification of one or more amino acids common to all these expressed peptides (Tables 1,2). The amino acid sequence of the first 22 residues of both bands was identical, as reported by Pfeifer et al (1999). Figure 1B and C compare Western blots of supernants from Kc1 cells transformed with preproITP cDNAs in which successive C-terminal amino acids were removed.…”
Section: Bioassayssupporting
confidence: 66%
“…Membranes were probed with antibodies made to amino acids 57-85 (underlined in Table 1) of the preproITP sequence at 1:10,000 dilution. The amount of expressed peptides was determined by densitometry as detailed in Macins et al (1999) and Pfeifer et al (1999). Band density on Western blots was first shown to be a linear function of concentration and then compared to known amounts of synITP.…”
Section: Western Blotting and Concentration Of Expressed Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila Kc1 cells transfected with pre-proITP secreted a peptide (KcITP) that was very active in the locust ileal bioassay and had the same time course of stimulation as native ITP. KcITP was correctly cleaved at the N-terminus, correctly folded, and co-migrated with SchgrITP and synITP on Western blots (King et al, 1999;Pfeifer et al, 2001). Site-directed mutagenesis and expression of KcITP mutants (Wang et al, 2000) indicated that amidated leucine (residue 72) at the C-terminus is essential for receptor stimulation.…”
Section: Introductionmentioning
confidence: 98%
“…The widely used baculovirus-Sf9 cell expression system was found to process preproITP incorrectly . This led us to use the plasmid vector p2Zop2F to transfect several cultured insect cell-lines (Pfeifer et al, 2001). Drosophila Kc1 cells transfected with pre-proITP secreted a peptide (KcITP) that was very active in the locust ileal bioassay and had the same time course of stimulation as native ITP.…”
Section: Introductionmentioning
confidence: 99%